Usefulness of endoscopic ultrasound in children with pancreatobiliary and gastrointestinal symptoms - Dalal, Ankit; Kamat, Nagesh; Patil, Gaurav; Daftary, Rajen; Maydeo, Amit (Endoscopy International Open, 2022)
Background and study aims Endoscopic ultrasound (EUS) is useful in diagnosing and treating childhood pancreatobiliary and gastrointestinal diseases. However, there are limited data on its effectiveness for various indications.Patients and methods This was a retrospective analysis of prospectively collected data of patients who underwent EUS for upper gastrointestinal tract disorders from January 2018 to December 2020 to assess its indications, findings, interventions, and complications.Results Ninety-two procedures were performed in 85 children, (70.5 % male; mean [SD] age 12.1 years [3.9] years) with a mean (SD) symptom duration of 1.1 (0.5) years. The procedures were technically successful in all patients. The primary indication for EUS was abdominal pain in 45(52.9%) and jaundice/cholangitis in 15 patients (17.6 %). General anesthesia was used in 12 (13 %) and TIVA in 80 patients (87 %). The most common diagnostic findings were choledocholithiasis in 21 (24.7 %) and cholelithiasis in 12 patients (14.1 %). Among interventions, EUS-guided cystogastrostomy for pancreatic pseudocyst was done in four patients (4.7 %), and EUS-guided rendezvous for failed ERCP in one patient (1.2 %) with cholangitis. There were no immediate post-procedural complications. Overall, EUS had a meaningful impact on the subsequent clinical management in 69 cases (81.2 %).Conclusions EUS in the pediatric population is safe, effective, and has a meaningful impact in appropriately selected cases. It can act as a rescue in major therapeutic procedures, but adequate care should be taken at the procedural level and during anesthesia.